Vanillin as an Antidote for Box Jellyfish (Chironex fleckeri) Envenomation - J, Vejayan; M.R, Mustaffa; M.M, Ali; M.M, Ali; I, Othman (Malaysian Journal of Science, 2007)
The phenolic compound, vanillin was tested and found to have potential anti-toxin activity against Chironex fleckeri toxin. Anti-toxin experiment conducted by premixing toxin and vanillin prior to intraperitoneal injection into mice showed that vanillin was able to completely neutralize the toxin in all 10 mice tested. It was also discovered that 0.5mg vanillin could ’rescue’ 7 out of the 10 mice previously envenomed with 68Âµg/kg of toxin. Haemolysis assay performed showed vanillin was capable of neutralizing the haemolytic effect of the toxin in a concentration-dependent fashion. The ICâ‚…â‚€ value of vanillin incubated with toxin at dilution giving 50% lysis (ECâ‚…â‚€) was determined to be 0.8mg/Âµg. Pharmacological studies using isolated rat aorta showed that 2ÂµM of vanillin was able to completely reverse the contraction induced by 0.1mg/ml toxin.